Neonatal Nav1.5 protein expression in normal adult human tissues and breast cancer - KAYA, HANDAN (ELSEVIER GMBH, 2017)
Expression of the neonatal splice variant of the voltage-gated sodium channel alpha-subunit (VGSC) subtype Nav1.5 (nNav1.5), encoded by the gene SCN5A, was shown earlier to be upregulated in human breast cancer (BCa), both in vitro and in vivo. Channel activity promoted BCa invasion of Matrigel (R) in vitro and metastasis in vivo. Consequently, expression of nNav1.5 has been proposed as a functional biomarker of BCa cells with metastatic potential. Here, we have determined immunohistochemically both nNav1.5 and total VGSC (tVGSC) protein expression in a range of adult human tissues. Some VGSC protein was expressed in normal colon, small intestine, stomach, prostate, bladder and breast. As expected, high levels of VGSC protein were expressed in brain, skeletal muscle and cardiac muscle. On the other hand, nNav1.5 protein was not expressed in any of the normal tissues tested except breast where a low-level of protein was present. In comparison to normal breast, nNav1.5 protein expression in BCa was consistently widespread and occurred at a significantly higher level. We also questioned whether there was any relationship between the nNav1.5 protein expression and the estrogen receptor (ER alpha) status of BCa and obtained the following results. First, all cases lacking nNav1.5 were positive for ERa. SOecond, in all ER alpha-negative tissues, nNav1.5 protein was expressed in plasma membrane. Third, however, in ER alpha-positive cases, nNav1.5 protein expression was observed in both plasma membrane and cytoplasm. In conclusion, nNav1.5 protein has a restricted expression pattern among human tissues. High level expression occurs in BCa and associates with ERa status. These results further support the proposition that nNav1.5 is a novel biomarker of metastatic BCa. (C) 2017 Elsevier GmbH. All rights reserved.
Keywords: Breast cancer; Metastasis; Voltage-gated sodium channel; Neonatal Nav1.5; Estrogen receptor; GATED SODIUM-CHANNELS; HUMAN PROSTATE-CANCER; FUNCTIONAL EXPRESSION; ESTROGEN-RECEPTOR; TUMOR GROWTH; INVASION; COLON; DISSEMINATION; INVASIVENESS; POTENTIATION